(untitled) - Patterson, David A. (Boston, 2014)
Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--Provided by publisher
Keywords: Tổ chức máy tính.,Computer organization